Grid-based multi-touch gesture to enhance two-factor authentication graphical password for mobile phones - Zabidi, Nur Syabila (2021)
This research focuses on the graphical password authentication, which combines image and emojis by implementing the use of multi-touch gesture that could provide an alternative to a textual password. The assumption of emojis is easier to remember and more secure has motivated the researchers to enhance existing graphical password authentication scheme. Nevertheless, several usability problems have been identified: (i) There is usually a lack of efficient methods in single-factor authentication to execute both usable and secure characteristics; (ii) The current approaches in graphical password authentication rarely combine image and emojis. The methodology used was the User- Centered Design approach, where the process starts with the understanding of needs, design, prototyping and assessment via a usability test. In this research, there are three fundamental studies, which included the preliminary study, the study of effects on grid-based two-factor authentication method and the study of single touch and multi-touch gestures for the application of graphical password authentication. The preliminary study examined user attitudes towards the usability and security of single-factor and two-factor methods for authentication in the context of graphical password application. The grid-based two-factor authentication study introduces recognition-based graphical methods that use emojis to resist several common threats to security without sacrificing the usability of the graphical password. Grid-based scheme enhanced the effectiveness of the graphical password with the success rate of 79%. The outcome of the single touch and multi-touch gesture study on graphical password authentication application has shown that the multi-touch gesture enhanced the user experience. The study on multi-touch gesture showed positive results, including increased success rates, and reduced completion times had been positively affected. This study provides the results that can be used to determine the technique of authentication that users prefer based on data collected during the preliminary study. This study also contributes to improved graphical password authentication, which can solve problems identified in studies, the picture superiority effect (P.S.E) in images and emojis. Furthermore, this research examines the impact of click and multi-touch gestures on the authentication of the graphical password. The results could be helpful for researchers or mobile developers interested in building a system that will advantage the research on picture and emojis using a graphical password authentication scheme. In future work, a comprehensive guideline for the development and verification of images and emojis, including a long-term assessment of these practices, should be included. The security of the prototype must also be examined closely and how attackers can take advantage of the emergence of hotspots. Overall, this study has introduced recognition-based graphical password methods that use emojis to resist several common threats to security without sacrificing the usability of the graphical password.